Immunomodulatory Effects of Papain in Patients with Cervical Ectopies - Dilorom Abdullaevna Musakhodjeva; Marufjon Abidovich Yuldashev; Neqqadam Abdullaevich Nuraliev; Rano Turdievna Sabitova; Gulnara Yangieva; Nigora Yakhayevna Fayzullaeva (International Journal of Public Health Science (IJPHS), 2014)
The study detected that in patients with cervical ectopia production of cytokines (TNFα, IL-4 и IL-10) was significantly altered. The degree of changedepended on the presence or absence of infection. Conducted therapy withherbal enzyme - papain contributed to the cupping of inflammation andnormalization of the concentration of the studied cytokines.